Efficacy of co-medications in patients with alcoholic liver disease - Itzel, Timo; Falconer, Thomas; Roig, Ana; Daza Barragán, Jimmy Andres; Park, Jimyung; Cheong, Jae Youn; Park, Rae Woong; Wiest, Isabella; Ebert, Matthias; Hripcsak, George; Teufel, Andreas (Digestive diseases, 2023)
Background: Alcoholic liver disease (ALD) is still increasing and leads to acute liver injury but also liver cirrhosis and subsequent complications such as liver failure or hepatocellular carcinoma (HCC). As most patients fail to achieve alcohol abstinence, it is essential to identify alternative treatment options in order to improve the outcome of ALD patients. Methods: Evaluating two large cohorts of patients with ALD from the USA and Korea with a total of 12,006 patients, we investigated the effect on survival of aspirin, metformin, metoprolol, dopamine, and dobutamine drugs in patients with ALD between 2000 and 2020. Patient data were obtained through the “The Observational Health Data Sciences and Informatics consortium,” an open-source, multi-stakeholder, and interdisciplinary collaborative effort. Results: The use of aspirin (p = 0.000, p = 0.000), metoprolol (p = 0.002, p = 0.000), and metformin (p = 0.000, p = 0.000) confers a survival benefit for both AUSOM- and NY-treated cohorts. Need of catecholamines dobutamine (p = 0.000, p = 0.000) and dopamine (p = 0.000, p = 0.000) was strongly indicative of poor survival. β-Blocker treatment with metoprolol (p = 0.128, p = 0.196) or carvedilol (p = 0.520, p = 0.679) was not shown to be protective in any of the female subgroups. Conclusion: Overall, our data fill a large gap in long-term, real-world data on patients with ALD, confirming an impact of metformin, acetylsalicylic acid, and β-blockers on ALD patient’s survival. However, gender and ethnic background lead to diverse efficacy in those patients.